Diels–Alder Cycloaddition of N-Azobenzene Maleimides with Furan and Electrochemical Study of Redox Reactions - David Fernando Venegas-Villalvazo; David Abraham Figueroa-Hernández; Armando Pineda-Contreras; José Manuel Flores-Alvarez; Héctor García-Ortega; Juan Saulo González-González (Reactions)
This work reports the synthesis of aminoazobenzene compounds derived from 3,5-dimethylaniline (1a–1f) via a diazo-coupling reaction with aromatic amines. These aminoazobenzenes were acylated with maleic anhydride to obtain the corresponding maleimides (2a–2f). The maleimides were then used as dienophiles in a Dies–Alder cycloaddition reaction with furan as the diene, yielding the adducts (3a–3f). All synthesized compounds were characterized using FTIR, 1H, and 13C NMR spectroscopy. Additionally, electrochemical studies using cyclic voltammetry were conducted to determine the oxidation–reduction reactions present in the compounds.